The craft of aging in place: identifying major constraints within the community - Griffin, Shelby E. (Kansas State University, 2011)
The aging demographic of the United States is growing at an alarming rate. Each day, there are more than 10,000 people turning 65 years old. The majority of these individuals prefer to live in their home, called aging in place. Aging in place requires the resident to be relatively independent and capable of accessing necessary services. The emergent demographic shift will compel every community across the country to focus community planning efforts toward older adults. The amenities and structures in a community are, most of the time, not favorable for the older demographic. People in their later years develop various medical and physical conditions and subsequently, find difficulty when adapting to the environment. These individuals definitely need extra care and consideration from all sectors of the community. Creating an environment that promotes aging in place for older adults is confronted with multiple barriers that a community must work past.
Keywords: Aging in place; Collaboration; Comprehensive planning; Geriatric; Land Use Planning (0536)